2021
DOI: 10.1590/s0034-759020210205
|View full text |Cite
|
Sign up to set email alerts
|

Export Performance in South America: Do Intangibles Affect Firms’ Performance in Developing Countries Such as Peru?

Abstract: This study is one of the first empirical studies on intellectual capital (IC) in South American textile exporting companies. Using the resources and capabilities approach, we examine how certain intangibles can provide competitive advantages. We propose and test a model capturing the relationships between IC components and export performance (EP), as well as the various interrelationships among the different dimensions of IC. Using a sample of textile manufacturers operating in Peru, an emerging economy, we fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…On the other hand, some authors found no direct positive relationship between CO and export performance (Arthur Solberg and Olsson, 2010;Guardamino and Ego avil, 2021). Instead, some authors found an indirect relationship (Zhang et al, 2020).…”
Section: Moderating Effect Of Customer Orientation Between Environmen...mentioning
confidence: 99%
“…On the other hand, some authors found no direct positive relationship between CO and export performance (Arthur Solberg and Olsson, 2010;Guardamino and Ego avil, 2021). Instead, some authors found an indirect relationship (Zhang et al, 2020).…”
Section: Moderating Effect Of Customer Orientation Between Environmen...mentioning
confidence: 99%